2013
DOI: 10.1177/0954411913496016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of head contact on the rim of the cup on the offset loading and torque in hip joint replacement

Abstract: Head contact on the rim of the cup causes stress concentration and consequently increased wear. The head contact on the rim of the cup may in addition cause an offset load and torque on the cup. The head-rim contact resulting from microseparation or subluxation has been investigated. An analytical model has been developed to calculate the offset loading and resultant torque on the cup as a function of the translational displacement of the head under simplified loading condition of the hip joint at heel strike … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Cup rim contact was considered as a result of a translational displacement of the head centre in the medial‐lateral plane relative to the geometric centre of the cup (Figure 2). 35 Both the cup and head version angles were chosen to be zero to match the corresponding set‐up in a simulator test20 for microseparation with a focus on cup inclination only. With this simplification, a half solid geometry can be used for the computational model25 by making use of the symmetry about the medial‐lateral plane (Figure 2), which also allows the FE model to have a substantially finer mesh with a relatively low computational time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cup rim contact was considered as a result of a translational displacement of the head centre in the medial‐lateral plane relative to the geometric centre of the cup (Figure 2). 35 Both the cup and head version angles were chosen to be zero to match the corresponding set‐up in a simulator test20 for microseparation with a focus on cup inclination only. With this simplification, a half solid geometry can be used for the computational model25 by making use of the symmetry about the medial‐lateral plane (Figure 2), which also allows the FE model to have a substantially finer mesh with a relatively low computational time.…”
Section: Methodsmentioning
confidence: 99%
“…Other boundary conditions included the position of the head centre being laterally fixed (along X ‐axis) corresponding to a given value of microseparation displacement, and the nodes on the outside surface of the cement being fully constrained. It should be pointed out that microseparation rim contact is a dynamic event,15, 18, 35 in which the head strikes the cup rim, and then slides on the cup rim back to the socket, and a complete analysis requires an advanced dynamic contact model. In this study, only an initial instant of the contact corresponding to the heel strike of a gait cycle was modeled and numerically solved as a quasi‐static contact18 between the head and cup rim rather than the full dynamic process.…”
Section: Methodsmentioning
confidence: 99%
“…Static modelling studies have considered deformation and damage and have shown that edge loading led to increased plastic strain [13][14][15], increased contact pressures [13][14][15][16][17], and increased liner peak von Mises stress [15]. It is also possible that edge loading contributes to disassociation of the acetabular cup from its fixation, with modelling showing the highest torque on the shell occurring at the highest separation [18].…”
Section: Introductionmentioning
confidence: 99%
“…14 In all bearing types, edge loading can cause an increased torque on the cup and potentially cup loosening. 15 In all types of hip prostheses, edge loading may lead to an increased rate of revision and failure.…”
Section: Introductionmentioning
confidence: 99%
“…4,[8][9][10][11][12][23][24][25] Edge loading may occur without dynamic (micro) separation, due to variation in rotational positioning alone, but there is increasing evidence that a mismatch between the relative positions of the centres of the cup and head leads to dynamic separation and severe edge loading, increased wear and damage and an increased torque at the cup surface. 8,[10][11][12]14,15,26 Clinically, the level of dynamic separation and severity of edge loading can vary considerably. 27 To be consistent with previous work, microseparation is used here to describe dynamic displacement of the centres of the head and cup of less than 1 mm and separation to describe dynamic displacements greater than 1 mm.…”
Section: Introductionmentioning
confidence: 99%